Early Hypertension and Diabetes After Living Kidney Donation: A National Cohort Study. Issue 6 (June 2019) - Holscher, Courtenay M.; Bae, Sunjae; Thomas, Alvin G.; Henderson, Macey L.; Haugen, Christine E.; DiBrito, Sandra R.; Muzaale, Abimereki D.; Garonzik Wang, Jacqueline M.; Massie, Allan B.; Lentine, Krista L.; Segev, Dorry L.
Abstract : Background: Living kidney donors have an increased risk of end-stage renal disease, with hypertension and diabetes as the predominant causes. In this study, we sought to better understand the timeline when these diseases occur, focusing on the early postdonation period. Methods: We studied 41 260 living kidney donors in the United States between 2008 and 2014 from the Scientific Registry of Transplant Recipients and modeled incidence rates and risk factors for hypertension and diabetes. Results: At 6 months, 1 year, and 2 years postdonation, there were 74, 162, and 310 cases, respectively, of hypertension per 10 000 donors. Donors who were older (per 10 y, adjusted incidence rate ratio [aIRR], 1.40; 95% confidence interval [CI], 1.29-1.51), male (aIRR, 1.31; 95% CI, 1.14-1.50), had higher body mass index (per 5 units, aIRR, 1.29; 95% CI, 1.17-1.43), and were related to their recipient (first-degree relative: aIRR, 1.28; 95% CI, 1.08-1.52; spouse: aIRR, 1.34; 95% CI, 1.08-1.66) were more likely to develop hypertension, whereas donors who were Hispanic/Latino were less likely (aIRR, 0.71; 95% CI, 0.55-0.93). At 6 months, 1 year, and 2 years, there were 2, 6, and 15 cases of diabetes per 10 000 donors. Donors who were older (per 10 y: aIRR, 1.42; 95% CI, 1.11-1.82), had higher body mass index (per 5 units: aIRR, 1.52; 95% CI, 1.04-2.21), and were Hispanic/Latino (aIRR, 2.45; 95% CI, 1.14-5.26) were more likely to develop diabetes. Conclusions: In this national study, new-onset diabetes was rare, but 3% of donors developed hypertension within 2 years of nephrectomy. These findings reaffirm that disease pathways for kidney failure differ by donor phenotype and estimate the population most at-risk for later kidney failure.